Non-pharmacological Interventions for Improving Sleep Quality During Pregnancy: A Systematic Review and Meta-Analysis - Daiane Sofia Morais Paulino; Carolina Bicudo Borrelli; Débora Bicudo Faria-Schützer; Luiz Gustavo Oliveira Brito; Fernanda Garanhani Surita (Revista Brasileira de Ginecologia e Obstetrícia, 2022)
Abstract Objective To investigate the effect of non-pharmacological interventions to improve sleep quality during pregnancy. Data sources A search was made in the NCBI/PubMed, ClinicalTrials.gov, Embase, BVS, and Web of Science databases. There were no limitations regarding language, sample size, and type of non-pharmacological intervention. We have included prospective clinical trials between July 2014 and July 2019. Selection of studies This study was registered in the Prospective International Registration of Systematic Reviews (PROSPERO) database was performed. Publication bias was also assessed with funnel plots. the primary outcome was the total score in the Pittsburgh Sleep Quality Index (PSQI) before and after intervention. Risk of bias and the Grading of Recommendations Assessment, Development, and Evaluation (GRADE) criteria were used for assessing methodological quality. From the 28 retrieved studies, we have selected 8 for qualitative analysis and 6 for meta-analysis. Data collection Two independent reviewers performed the study selection. In the case of disagreement, a third senior reviewer was consulted. The study was initially assessed based on the title, followed by abstract. Lastly, the full text was assessed to be included. Data Synthesis A significant improvement on the sleep quality (PSQI score) was observed when all interventions were grouped (MD = -3.03, 95%CI -4.15 to -1.92, n= 623, i2= 84%, p< 0.001). Analysis by subgroup (music listening: MD = -1.96, 95% CI -3.27 to -0.65, n= 207, i2= 67%, p= 0.003 and other interventions: MD = -3.66, 95% CI -4.93 to -2.40, n= 416, i2 = 80%, p< 0.001) showed an improvement, with high heterogeneity. Risk of bias has shown performance and detection bias for almost studies, and GRADE evidence was very low for all analyzed variables. Conclusion Non-pharmacological interventions—listening to music, physical exercise, relaxation exercises, lettuce seed, sleep hygiene, and acupressure—are effective for improving sleep quality during pregnancy.